2018
DOI: 10.4236/ojmetal.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Characterization of Chicken Eggshell-Reinforced Al6061 Matrix Composites

Abstract: Chicken eggshell (ES) is an aviculture byproduct that has been used as the reinforcement in the present study which is recorded worldwide as one of the vilest environmental problems. The present work deals with development of ES-reinforced Al6061 matrix composites by stir-casting process with 0 to 10 wt% of reinforcement at an interval of 2 wt%. The microstructures of the fabricated composites were examined by optical and scanning electron microscopes with energy dispersive spectrometer (SEM/EDS). Optical micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…1 shows a high peak of Al as a major element while other elements such as Fe, Zn, Mg, Si, Cu, Mn, and Cr, are by the element composition. The compositions simply confirm that the alloy is typical of Al 6061 [ 31 ].
Fig.
…”
Section: Methodsmentioning
confidence: 72%
“…1 shows a high peak of Al as a major element while other elements such as Fe, Zn, Mg, Si, Cu, Mn, and Cr, are by the element composition. The compositions simply confirm that the alloy is typical of Al 6061 [ 31 ].
Fig.
…”
Section: Methodsmentioning
confidence: 72%
“…From the findings of Dwiwedi et al [7] and Ibrahim et al [8], one essential factor that limits the application of aluminum metal matrix composites is their high cost of production due to the use of expensive synthetic reinforcements such as SiO 2 , Al 2 O 3 , SiC, etc. To overcome this obstacle, researchers have shifted their focus to utilizing low-cost and lowdensity reinforcements such as eggshells, pumice, bagasse, carbonated coal, and others [1,3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al [23] investigated FSPed Al/Egg shell/SiC and showed that the hardness and tensile strength improved in the processed material. Dwiwedi et al [24] discussed the potential reduction in mechanical properties, when ESP added to the metal matrix above 4% by stir casting process. The decrease in mechanical properties is because of porosity.…”
Section: Introductionmentioning
confidence: 99%